Managing business model innovation in a changing environment: The case of SMEs in the pharmaceutical sector - Chabanet, Didier; Do Vale, Guillaume; Weppe, Xavier (Management international / International Management / Gestiòn Internacional)

(untitled) (HEC Montréal, 2024)
This paper seeks to understand how owner-managers’ perceptions of environmental changes led them to adapt their business model (BM). Drawing on 43 interviews with independent pharmacist in Belgium (19) and Italy (24), we demonstrate how some owner-managers focus on their macro-environment leading them to consider environmental changes as a threat. They feel they are unable to adapt their BM or only provide minor adaptation. However, some owner-managers focus both on their micro and macro-environment, sometimes beyond the traditional pharmacy sector, to identify opportunities. They then extricate themselves from the constraints perceived in the environment to proceed with significant BM innovation by building a specific ecosystem.